When bodies think: panpsychism, pluralism, biopolitics. Issue 2 (9th July 2019) - Savransky, Martin
Abstract : Cultivating a speculative orientation to the medical humanities, the aim of this essay is to explore some dimensions of the recent calls for more participatory forms of medicine and healthcare under the sign of what, after Michel Foucault, I call the 'biopolitical problematic'. That is, the divergent encounter between techniques of biopower that seek to take hold of life and the body, and a plurality of living bodies that persistently respond, challenge and escape its grasp. If critics of 'participatory medicine' have warned that the turn to 'participation' in healthcare functions as a form of biopower that seeks to gain access to bodies, and in so doing take a better hold of life, in this essay, I propose we experiment with the question of what kinds of conceptual tools may be required to make perceptible the ways in which a plurality of participating bodies may become capable of responding, challenging and escaping 'participation's' grasp. After problematising the ontology of participation involved in contemporary debates around participatory medicine, I draw on the work of William James and Alfred North Whitehead, among others, to argue for the need to reclaim a pluralistic panpsychism—in short, the proposition that all things think—as a pragmatic tool to envisage the possibility of a plurality of thinking bodies capable of unruly forms of participation all the way down.